Learner Perceptions and Teacher Beliefs about Learner Autonomy in Language Learning - Joshi, Khem Raj (Journal of NELTA, 2012)
Learner autonomy is one of the intriguing phenomena in the field of SLA. This has become the focal point for many scholars and researchers these days. The present study was carried out to make a survey of autonomous learning activities of the Master level students, majoring in English Education, Tribhuvan University, Nepal. It also explored their perceptions on the roles of their own and their teachers’ roles, and how it has been looked at from the teachers’ viewpoint. Adopting a mixed methodological design and analyzing the data collected through questionnaire and semi-structured interview, it was found that the learners make a good practice of autonomous activities. They view their role as an important factor in learning. The teachers have also suggested the learners to be autonomous. The teachers as well as the learners were found highly positive towards autonomous learning. DOI: http://dx.doi.org/10.3126/nelta.v16i1-2.6126 NELTA 2011; 16(1-2): 13-29